Prevalence of Polycystic Ovary Syndrome in Infertile patients of Janakpurdham, Nepal (Janaki Medical College Journal of Medical Science, 2021)
Background and Objectives: The overall prevalence of PCOS varies in different population and is influenced by multiple factors like genetic predisposition, ethnicity, associated metabolic disorders environmental factors, unhealthy diet and so on. This study is planned to assess the prevalence of polycystic ovary syndrome among infertile women of Janakpur seeking treatment for infertility.Material and Methods: This study is a cross sectional study conducted in Janakpur among women who attended outpatient department for infertility treatment over a period of one year.Results: Polycystic Ovarian Syndrome (PCOS) as per Rotterdam criteria was found among 7.30% infertile women of Janakpur. Prevalence of Oligo/anovulation was 13.95%. Hirsutism was found in 6.47% women and polycystic ovaries were found in 17.94% women in transabdominal scan.Conclusions: In this study prevalence of PCOS was found lower than that of other similar studies. There is a need of studying a larger population to establish the prevalence rate of PCOS in Nepalese women.